2012
DOI: 10.1128/jb.06814-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Facultative Anaerobic Arsenite-Oxidizing and Nitrate-Reducing Bacterium Acidovorax sp. Strain NO1

Abstract: c Acidovorax sp. strain NO1, isolated from gold mine soil, was shown to be a facultative anaerobic arsenite-oxidizing and nitratereducing bacterium. The reported draft genome predicts the presence of genes involved in arsenic metabolism, nitrate reduction, phosphate transport, and multiple metal resistances and indicates putative horizontal gene transfer events.A cidovorax sp. strain NO1 was isolated from arseniccontaminated soil of a gold mine in Daye, Hubei Province, China. It is highly arsenic resistant, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 16 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…Therefore, the arsenic-related gene may have very early origins, especially the ars-like gene. This speculation was supported in part by recent literatures showing that bacterial arsenic resistance and transformation was an acquired trait via HGT, driven by adaptation to habitats containing arsenic [17], [19], [43][45]. However, we found that the arsenic-related genes were absent in ten of the 188 examined strains, which suggest that some microbes may lose their arsenic-related genes during adaption to arsenic-free niches.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the arsenic-related gene may have very early origins, especially the ars-like gene. This speculation was supported in part by recent literatures showing that bacterial arsenic resistance and transformation was an acquired trait via HGT, driven by adaptation to habitats containing arsenic [17], [19], [43][45]. However, we found that the arsenic-related genes were absent in ten of the 188 examined strains, which suggest that some microbes may lose their arsenic-related genes during adaption to arsenic-free niches.…”
Section: Discussionsupporting
confidence: 80%
“…The enrichment of Asticcacaulis in the family Caulobacteraceae might be caused by the attraction of the plant exudations, because these bacteria are adhesive and aerobic heterotrophs commonly found in freshwaters (30). Many members of Comamonadaceae, especially the genus Acidovorax (31)(32)(33), are frequently detected as denitrifiers coupled with the degradation of organic substrates in wastewater treatment plants (31,34). Species of Methylibium can also reduce nitrate into nitrite, and more importantly, they are capable of using methanol as a sole carbon source (35).…”
Section: Discussionmentioning
confidence: 99%
“…Within the Burkholderiales Order, two genera Polaromonas and Aquabacterium that were found in the BCR are frequently associated with hydrocarbon degradation in contaminated soils [43,44]. Another Burkholderiales genus present in the BCR, Acidovorax, includes species capable of arsenite oxidation [45]. Genera within the Rhizobiales Order (e.g., Rhizobium) were closely related to metal-tolerant species that might play a role in metal sequestration [45,46].…”
Section: Othersmentioning
confidence: 99%
“…Another Burkholderiales genus present in the BCR, Acidovorax, includes species capable of arsenite oxidation [45]. Genera within the Rhizobiales Order (e.g., Rhizobium) were closely related to metal-tolerant species that might play a role in metal sequestration [45,46]. Genera found within the Caulobacterales Order (Caulobacter and Brevundimonas) are ubiquitous in many different environments.…”
Section: Othersmentioning
confidence: 99%